Sifat-sifat Mekanik Komposit Serat TKKS-Poliester - Shirley Savetlana (JURNAL MECHANICAL, 2012)
Abstract Empty Fruit Bunch (EFB) fiber reinforced polyester composites were prepared using simple technique namely hand lay-up. Alkali treatments were used to enhance the hydrophobicity of the fiber. Lignin and cellulose content of EFB were analysed through chemical composition analysis. The mechanical properties are analyzed by conducting tensile and flexural tests. Macro observation shows fiber bridging on the fracture section. The SEM micrograph also shows a better surface roughness after alkali treatmen. The result shows that bending strength increases with the increases of fiber volume fraction.  Tensile strength and elastic modulus of composite were higher than the pure polyester and increases with the increasing of fiber volume fraction although polyester shows low compatibility with the EFB fiber. The failure mechanism as a result of bending and tensile tests had shown a dominant fiber pull-out mechanism and less of fiber breaking mechanism. It suggests that the optimal strength of the composite can be further increases by enhancing the compactibility between fiber and matrix.Keywords: EFB fiber, mechanical properties, polyester, composite, hand lay-up